Thermal behavior of alpha-(Cu-Al-Ag) alloys - Adorno, A. T.; Silva, R. A. G.; Magdalena, A. G. (Springer, 2007)
Thermal behavior of alpha-(Cu-Al-Ag) alloys, i.e. alloys with composition less than about 8.5 mass% Al, was studied using differential scanning calorimetry (DSC), differential thermal analysis (DTA), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX) and X-ray diffractometry (XRD). The results indicated that the presence of silver introduces new thermal events ascribed to the formation of a silver-rich phase and, after addition higher amounts than 8 mass% Ag to the Cu-8 mass% Al alloy it is possible to observe the formation of the gamma(1) phase (Al4Cu9), which is only observed in alloys containing minimum of 9 mass% Al. These results may be attributed to some Ag characteristics and its interaction with Cu and Al.
Keywords: Ag-Al interaction; copper-based alloys; silver additions; thermal behavior